Ceramic matrix composites : materials, modeling and technology / edited by Narottam P. Bansal, Jacques Lamon. - Bansal, Narottam P.; Lamon, Jacques (Wiley, 2015)
A comprehensive source of information on various aspects of ceramic matrix composites (CMC). It covers ceramic and carbon fibers; the fiber-matrix interface; processing, properties and industrial applications of various CMC systems; architecture, mechanical behavior at room and elevated temperatures, environmental effects and protective coatings, foreign object damage, modeling, life prediction, integration and joining.